Assessment of the quality of life according of the sf-36 questionnaire in adolescents with primary hypertension [Lublin] - Patsera, M. V.; Tovma, A. V.; Skrypnykova, Yа. S.; Пацера, Марина Вікторівна; Товма, Анастасія Володимирівна; Скрипникова, Яніна Семенівна (Medical University of Lublin, 2021)
Introduction. The priority area in the study of the etiological factors of arterial hypertension (AH) is genetic research. Single nucleotide polymorphisms (SNPs) of genes of the NFATC (nuclear factor of activated T-cells) family do not directly affect blood pressure (BP) in humans but can participate in the formation of an unfavorable course of AH. Among the most important SNPs of the NFATC4 gene, rs2229309 (Gly160Ala), which affects the development of cardiac hypertrophy, can be noted [1, P. 435]. Previously, we have established the prevalence of the occurrence of the G rs2229309 allele of the NFATC4 gene in the genotypes of adolescents with primary AH, with early formation of left ventricular hypertrophy. Further research aimed at phenotyping variations in the NFATC genes could be promising for the future study of the pathogenesis and clinical manifestations of AH in young people. Modern approaches to assessing the quality of life (QoL) represent a clinical approach to identifying disorders of the patient’s health status by analyzing the system of signs that make up the concept of general health.